Response of One-Way Reinforced Masonry Flexural Walls under Blast Loading - Hayman, Mark (My University, 2014)
In this thesis, the dynamic structural response of six scaled flexural masonry walls to scaled blast loading is experimentally investigated. These walls have been tested in at an open range with charge masses ranging from 5 kg to 25 kg of Pentex-D explosive material with a TNT equivalency of 1.2, and with a constant stand-off distance of 5 m throughout testing. The field properties of the blast wave, which includes the reflected and free field pressures, were recorded. Additionally, the displacement response histories of the wall over the blast test were recorded and the post-blast damage was documented. This study puts forth several potential models for the analysis of the experimental data. The experimentally obtained blast characteristics were compared to predictions of the Kingery and Bulmash (K-B) model. The strain rates used during the study are equivalent to those developed by a number of studies for the materials used in the construction of the specimens. The results obtained through the experimental program are compared to those from a variety of single degree of freedom models, ranging from simplified linear relationships to complex stress-strain relations accounting for the effects that arise because of the increased strain rate due to blast testing. The simplified model assumes a constant stiffness, mass, and triangular pressure profile to determine the peak deflection of the specimen during an experimental test. The bilinear and nonlinear models are based on the discretization of the wall sections into a number of layers, and using strain-rate dependent, stress-strain relations of the constituent materials to generate stresses within the layers. These stresses then iv form the basis of the resistance function to determine the structural response of the test specimens. In this study, the effect of higher modes of vibration on the test specimens is not included. The bilinear and nonlinear models are then implemented to develop Pressure-Impulse (P-I) diagrams, and the effect of the strain rate on P-I diagrams is investigated. The P-I are then available to be implemented into the recent blast code for reinforced masonry flexural walls. The fitted results of the recorded experimental blast pressure parameters are shown to be adequately approximated by the software ConWep in terms of the peak pressure and specific impulse. Comparing the K-B model, which forms the theoretical basis of ConWep, to the raw pressure profile data obtained from the experimental testing, a significant variations is found in the pressure data while significant scatter is found in the impulse. The analytical results show that increasing the nonlinearity of the material accounts for; the response predicted by the single degree of freedom model more closely relates to the response of the specimens. In addition, strain rate effects have a significant impact on the potential level of protection (LOP) provided by masonry flexural walls, as it has a noticeable effect on the curves of the P-I diagram.
Keywords: Blast Loads; Concrete Masonry; Reinforced Masonry Blast Response; Third-Scale Testing; Nonlinear SDOF Model; Strain Rate; Pressure-Impulse